2015
DOI: 10.1088/1367-2630/17/8/083060
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium transport through a model quantum dot: Hartree–Fock approximation and beyond

Abstract: The finite-temperature transport properties of the spinless interacting fermion model coupled to noninteracting leads are investigated. Employing the unrestricted time-dependent Hartree-Fock (HF) approximation, the transmission probability and the nonlinear I-V characteristics are calculated, and compared with available analytical results and with numerical data obtained from a Hubbard-Stratonovich decoupling of the interaction. In the weak interaction regime, the HF approximation reproduces the gross features… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Finally, we note that in our approach, similar to most earlier studies of quantum dot heat engines, the Coulomb interaction among electrons, both within the dots and between neighboring dots, was not considered. In the limit of weak correlations, it is possible to retain the Landauer picture of noninteracting particles by using decoupling schemes like the Hartree [28] or the Hartree-Fock [29] approximation, which roughly corresponds to taking screening into account [28]. Other heat engine designs, which utilize Coulomb blockade physics, have also been discussed [2,[12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that in our approach, similar to most earlier studies of quantum dot heat engines, the Coulomb interaction among electrons, both within the dots and between neighboring dots, was not considered. In the limit of weak correlations, it is possible to retain the Landauer picture of noninteracting particles by using decoupling schemes like the Hartree [28] or the Hartree-Fock [29] approximation, which roughly corresponds to taking screening into account [28]. Other heat engine designs, which utilize Coulomb blockade physics, have also been discussed [2,[12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Refs. 15,35 showed that the NDC in the IRLM is already obtained at the Hartree-Fock (HF) level. Therefore, it is interesting to investigate if the mechanism leading to the NDC obtained from our results is qualitatively similar to the one in the HF approximation.…”
Section: B Negative Differential Conductancementioning
confidence: 99%